Formulation and Evaluation of Sustained Release Bilayer Tablets of Losartan Potassium (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Heart disease is very common cause of deaths in the world. Hypertension is the most prevalentform of heart disease. Losartan has wonderful clinical effectiveness in the treatment of essential hypertensionand congestive heart failure. Single dose of losartan can maintain the lowering of blood pressure up to 6–8 h.Hence, repetitive medication is required in a day to maintain the blood pressure. Hence, the aim of this work isto formulation and evaluate of sustained release (SR) bilayer tablet of losartan potassium in which the immediaterelease layer will release the drug within 10 min and SR layer will maintain uniform drug levels over a sustainedperiod of time. Materials and Methods: This research work is performed for the partial fulfillment of thedegree of master of pharmacy. The tablets were evaluated to thickness, hardness, diameter, weight variation,drug content uniformity, friability, and in vitro drug release studies. In vitro drug release studies were performedusing USP type II apparatus (paddle method) at 50 rpm in 900 ml of 0.1N HCl as dissolution medium for first 2 hand later replacing it with 900 ml pH 6.8 phosphate buffer solution for the remaining time period at 37±0.5°C.Results: The results of Fourier transform infrared and differential scanning calorimetry analysis showed that therewas no physical and chemical interaction between drug and other excipients. The stability studies of optimizedformulation ME5 at 400C/75%RH for 3 months did not show any variation in the tasted parameter and release.